THE IMPLICATIONS OF POPULATION AGING ON LOCAL HEALTH CARE EXPENDITURE: A 22-YEAR PANEL DATA ANALYSIS - Eyitayo Francis Adanlawo; Nomusa Yolada Nkomo (International Journal of Innovative Technologies in Social Science, 2023)
The purpose of this study is to examine the implications of population aging on local health expenditures in South Africa. A balanced panel of annually observed observations from South Africa over the period of 22 years (1995–2017) was used. The study used gross domestic product (GDP), health expenditure, labor force, and age structure as control variables and pooled OLS, fixed effect, and random effect tests to estimate the relationships among the variables. The results show that the old-age dependency ratio, gross domestic product (GDP), unemployment rate, and gross value added (GVA) are all explanatory variables that are related to healthcare spending and are shown as a base model in the pooled OLS. The results indicate that healthcare expenditure and the old-age dependency ratio have a positive relationship in South Africa. Considering the implications for policy, this study suggests that the South African economy should account for the aging population when policies are designed and that the government should make an effort to improve the healthcare system in order to meet the demands of elderly people.